The quality of the auditor's report in the local environment in compliance with the requirements of the ISA 701 standard - Ali, Haya Ayad; Ibrahim, Lubna Zaid (Journal of Economics and Administrative Sciences, 2020)
The research aims to demonstrate the quality of the auditor’s report by analyzing a number of models represented by the auditor’s report based on the Iraqi audit evidence and the auditor’s report in light of the application of international auditing standards for the report and the auditor’s report in light of the application of the International Auditing Standard 701, in addition to explaining the impact of applying the International Auditing Standard 701. International Auditing 701 in enhancing the quality of the auditor's report, and in order to reach these goals, a comparison was made on international experiences before and after the application of the standard in addition to the results of the questionnaire distributed to auditors in the Iraqi environment in the Federal Office of Financial Supervision and private offices. To a set of conclusions, the most important of which was the apparent deficiency in the Iraqi audit legislation and evidence, especially the local audit manual (2) as it lacked many things because it did not include many of the paragraphs of the new auditor’s report in the world compared to the international auditing standard 700, the most important of which is the reporting paragraph On the important matters in accordance with Standard 701, as well as the different contents of the accounts of the auditors' reports in Iraq, each according to the duration To be informed, convinced, experienced, and adhered to international auditing standards and local audit evidence. And that the majority of account auditors in the Iraqi environment do not adhere to the Iraqi and international auditing standards, and this greatly affects the accuracy of the information contained in the Iraqi report as it is the means used to inform the data users of the opinion of the neutral technical auditor, as they claim that they are reporting important audit matters from Throughout the explanations section they present in their reports relying on Iraqi audit evidence, as they assume that the users concerned with their reports are rational, and this does not mean abandoning the responsibility to protect the interests of those users in all circumstances.